Distribution, associated vegetation, conservation and utilization of Grewia tenax: an important underutilized shrub species of the Thar Desert of India. Issue 1 (5th November 2018) - Venkatesan, K.; Patidar, Anil; Singh, Maharaj; Kumar, Mahesh; Kumawat, R. N.; Dev, Rahul; Uchoi, Julius; Kumar, Abhishek; Mertia, D. S.; Singh, J. P.
Abstract: Grewia tenax locally known as ' Gangerun ', is an important multipurpose underutilized shrub and potentially threaten species of the Thar Desert of India. Owing to its importance, naturally available germplasm was collected and evaluated for its sustainable utilization in future. Data on individual mother plant, seed characters and soil profile were investigated. Habitat occurrence of G. tenax was found in patches with dominant association of Euphorbia caducifolia across the four districts of western Rajasthan. Individual plant on unprotected area portrayed far lower average height (0.95 m) and canopy area (1.75 m 2 ) than protected area (2.63 m and 13.89 m 2 ) signifying level of browsing pressure on this species in Jaisalmer. Soil samples belonging to Pali region have high organic carbon and low electrical conductivity content than Jaisalmer and Jodhpur. The statistical analysis of seed characters revealed the presence of high coefficient of variation (%) in 100-seed weight (HSW; 27.36) followed by seed length (SL; 8.06) and least in seed breadth (SB; 5.85). The range and mean values of HSW, SL, SB and length:breadth ratio (LBR) were (2.02–7.00 and 3.34 g), (4.36–6.15 and 5.36 mm), (3.73–4.68 and 4.25 mm) and (1.11–1.44 and 1.27), respectively. Significantly positive correlation was observed between SL and LBR (0.73) followed by HSW and SL (0.66). Along with these findings, its economic importance, utilization and conservation are detailed in this paper as to hasten further research on its various aspects for its successful conservation and utilization.